2012
DOI: 10.1063/1.4711769
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier inhomogeneities at the interface of few layer epitaxial graphene and silicon carbide

Abstract: In this work, we study electron transport across the heterojunction interface of epitaxial few-layer graphene grown on silicon carbide and the underlying substrate. The observed Schottky barrier is characterized using current-voltage, capacitance-voltage and photocurrent spectroscopy techniques. It is found that the graphene/SiC heterojunction cannot be characterized by a single unique barrier height because of lateral barrier inhomogeneities. A Gaussian distribution of barrier heights with a mean barrier heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…As can be seen from this histogram, the Schottky barrier height at the graphene/SiC heterointerface is strongly sensitive to the growth method and the graphene thickness. Furthermore, as was reported earlier, the unintentional presence of unavoidable natural ripples and ridges in epitaxial graphene on SiC may also cause the fluctuations in the Schottky barrier height [49][50][51][52][53][54]. The key factors influencing the uniformity of the Schottky barrier height for graphene/SiC structures are the homogeneity of the graphene thickness, the quality of the grown interface (defects, pits, dislocations, surface roughness), the kind of grown interface (SiC polytypism, face polarity) and the growth conditions.…”
Section: Experimental Control Of the Barrier Height At The Graphene/smentioning
confidence: 76%
“…As can be seen from this histogram, the Schottky barrier height at the graphene/SiC heterointerface is strongly sensitive to the growth method and the graphene thickness. Furthermore, as was reported earlier, the unintentional presence of unavoidable natural ripples and ridges in epitaxial graphene on SiC may also cause the fluctuations in the Schottky barrier height [49][50][51][52][53][54]. The key factors influencing the uniformity of the Schottky barrier height for graphene/SiC structures are the homogeneity of the graphene thickness, the quality of the grown interface (defects, pits, dislocations, surface roughness), the kind of grown interface (SiC polytypism, face polarity) and the growth conditions.…”
Section: Experimental Control Of the Barrier Height At The Graphene/smentioning
confidence: 76%
“…It can be used to determine the impurity states and defect centers in the semiconductor, which in turn evaluate the structural and physical parameters of the photodiodes [10]. However, previous works with investigation of the dynamic properties of the 4H-SiC-based photodiodes mostly focus on the Schottky structure [11][12][13][14]. The C-V characteristics of the 4H-SiC p-i-n photodiodes have not been fully investigated so far.…”
Section: Introductionmentioning
confidence: 97%
“…5,[14][15][16][17][18] While these fluctuations can be related to the number of graphene layers, (e.g., epitaxial graphene on SiC typically consists of one to three layers on a warped interface layer, 19 and exfoliated and chemical vapor deposited (CVD) graphene studied are typically single layer,) 20 the impact of spatial inhomogeneity has not been fully considered, particularly when graphene is normally susceptible to form ripples and ridges upon interfacing with another material. 13,21 Shivaraman et al 22 have speculated lateral barrier inhomogeneities as the possible cause for different SBHs obtained from C-V and I-V measurements for few layer EG/Si-SiC junction. Tadjer et al 23 have recently shown that the variation in SBH can be related to step length in EG/4H-SiC(0001).…”
mentioning
confidence: 99%